Seasonal plasticity of song behavior relies on motor and syntactic variability induced by a basal ganglia–forebrain circuit - Alliende González, Jorge Andrés (2017)
Fil: Alliende González, Jorge Andrés. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina.